Two decades without the father of the pedagogy of liberation - J. Ignacio “Iñaki” Chaves G (Revista Kavilando, 2017)
Freire is a reference in Latin American social thought, his figure and his work have accompanied critical bets by another education, problematizing, liberating and emancipating a society that has been under the oppression of a political and educational system colonizing and excluding. To review him is a necessity to keep in mind his work and the importance of his writings.